Mobile learing acceptance among students of Ramkhamhaeng University, Thailand - Madarsha, Kamal Basha; Matha, Wanchat (Faculty of Education Yala Rajabhat University, 2013)
The rapid growth of mobile technology will push educational institutions to adopt mobile learning (m-learning). It has the potential to allow students to more closely integrate with learning activities in their lives. However, its adoption and level of use is low in Thailand compared to other countries. This study aims to identify factors that affect the adoption of m-learning in Thailand. The technology Acceptance Model (TAM) is used as theoretical framework towards understanding the adoption of m-learning. The quantitative method was applied to collect primary data from 200 Ramkhamhaeng University (RU) students who use m-learning. The findings reveal that only three factors contributed significantly towards adoption of m-learning among RU students. The factors were Thai Social Influence, Student Readiness, and Quality of Content. Thai Social Influence was found to be the most influential factor in the model. On the other hand, factors such as Perceived Usefulness, Perceived Ease of Use, and Network Accessibility were found to insignificantly contribute predictors on m-learning adoption. This research provides useful information in the understanding students’ acceptance of m-learning in RU. Moreover, it also gives perspectives to RU and other institutions who want to integrate m-learning system into their curricula.